Investigating The Effects of Activation Temperature on The Crystal Structure of Activated Charcoal From Palm Bunches (Arengga Pinnata Merr.) - Mongkito, Vivi Hastuti Rufa; Anas, Muhammad; Bahar, Wisda Puspita (Universitas Ahmad Dahlan, 2019)
This research aims to determine the effect of activation temperature the crystal structure of activated charcoal. The material used activated charcoal bunches (Arengga Pinnate Merr). The process of making activated charcoal divided into two, namely the carbonization stage at a temperature of 250- 400 oC and the activation stage at a temperature variation of 600 - 800 ̊C. To find the crystal structure, the sample characterized by X-Ray Diffraction. The results of analysis the dominant elements diamond before activation with a percentage of 90.2% and an orthorhombic crystalline structure, where the lattice parameter a = 4.12700 Å; b = 4.93700 Å; c = 4.81900 Å. Peak Carbon has a hexagonal crystal structure in all temperature variations. Peak Graphite an orthorhombic crystal structure and at a temperature of 700 oC a hexagonal crystal structure formed. Therefore, giving temperature variations the activated charcoal of the bunches affects the structure of the formed Crystal. Wherein increasing the activation temperature, the crystal structure that forms look more amorphous marked by a widening diffraction peak intensity decreased crystals